2022
DOI: 10.3389/fimmu.2022.801909
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Anti-PD1/PDL1 in Advanced Biliary Tract Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundAnti-programmed cell death protein 1 and its ligand (anti-PD1/PDL1) have been proposed as a promising therapeutic option for advanced biliary tract cancer (aBTC). Given the scarce quantitative analyses of anti-PD1/PDL1 in aBTC, we thus did a meta-analysis to assess the benefits and risks of this emerging treatment strategy in patients with aBTC.MethodsPubMed, Embase, the Cochrane Library, Web of Science, and meeting resources were searched for relevant studies. The main endpoints were median progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Similar to the findings of Zhu's study, early use of immunotherapy and chemotherapy combined with targeted therapy is recommended for patients who are able to tolerate it 24 . Additionally, a recent meta‐analysis of the efficacy of anti‐PD‐1/PD‐L1 in advanced BTC showed that median OS was longer in the first‐line settings than in the second‐line settings or beyond 25 …”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Similar to the findings of Zhu's study, early use of immunotherapy and chemotherapy combined with targeted therapy is recommended for patients who are able to tolerate it 24 . Additionally, a recent meta‐analysis of the efficacy of anti‐PD‐1/PD‐L1 in advanced BTC showed that median OS was longer in the first‐line settings than in the second‐line settings or beyond 25 …”
Section: Discussionmentioning
confidence: 55%
“…24 Additionally, a recent meta-analysis of the efficacy of anti-PD-1/PD-L1 in advanced BTC showed that median OS was longer in the first-line settings than in the second-line settings or beyond. 25 Peripheral blood inflammation scores have great potential in predicting the efficacy of immunotherapy and have been reported in a variety of tumors, such as hepatocellular carcinoma, 26 non-small cell lung cancer, 27 and pancreatic cancer. 28 Several studies have shown that inflammation scores can be used as a predictor of response to anti-PD-1 in patients with BTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed cell death 1/programmed cell death ligand 1 (PD1/PDL1) enhances tumor resistance to immuneinduced apoptosis and promotes tumor growth. Targeting the PD1/PDL1 axis can effectively inhibit tumor progression and improve patients' OS [69][70][71][72][73][74][75][76][77][78]. We found that several immune cells and immunological checkpoints were differentially expressed in the two risk subgroups after performing immune cell infiltration and immune checkpoint analyses using the CESC prognostic model.…”
Section: Discussionmentioning
confidence: 83%
“…Various drugs, including conventional chemotherapeutic agents, anti-angiogenic agents, and inhibitors targeting other immune checkpoints (e.g., cytotoxic T lymphocyte-4), have been introduced in combination regimens with anti-PD-1/PD-L1 agents for the treatment of BTC ( 27 , 28 , 30 , 37 ). A recent meta-analysis involving patients with BTC showed superior treatment response and clinical outcomes using combination regimens with anti-PD-1/PD-L1 therapy compared to anti-PD-1/PD-L1 monotherapy ( 58 ). This was consistent with our results, which demonstrated a higher response rate in combination therapy.…”
Section: Discussionmentioning
confidence: 99%